Seroepidemiology of Toxoplasmosis among Pregnant Women in Hamadan City - Mohammad Fallah; Mohammad Matini; Heshmatollah Taherkhani; Soghra Rabiee; Mehrdad Hajiloei (پزشکی بالینی ابن سینا, 2006)
Introduction & Objective: Toxoplasmosis is one of the most widespread parasitic infections in the human beings and other warm-blooded animals that can cause chronic infection in adults, fatal illness in immunodeficient patients and abortion in pregnant women or congenital abnormalities in fetus. The aim of this study was determination of the prevalence of toxoplasmosis in primigrvida women in Hamadan.